Spherical core–shell alumina support particles for model platinum catalysts. Issue 7 (15th February 2021) - Geerts, Lisa; Geerts-Claes, Hannelore; Skorikov, Alexander; Vermeersch, Julie; Vanbutsele, Gina; Galvita, Vladimir; Constales, Denis; Chandran, C. Vinod; Radhakrishnan, Sambhu; Seo, Jin Won; Breynaert, Eric; Bals, Sara; et al.
Abstract : Pt loaded alumina spheres, combined with a zeolite, are presented as a flexible model bifunctional catalyst. Abstract : γ- and δ-alumina are popular catalyst support materials. Using a hydrothermal synthesis method starting from aluminum nitrate and urea in diluted solution, spherical core–shell particles with a uniform particle size of about 1 μm were synthesized. Upon calcination at 1000 °C, the particles adopted a core–shell structure with a γ-alumina core and δ-alumina shell as evidenced by 2D and 3D electron microscopy and 27 Al magic angle spinning nuclear magnetic resonance spectroscopy. The spherical alumina particles were loaded with Pt nanoparticles with an average size below 1 nm using the strong electrostatic adsorption method. Electron microscopy and energy dispersive X-ray spectroscopy revealed a homogeneous platinum dispersion over the alumina surface. These platinum loaded alumina spheres were used as a model catalyst for bifunctional catalysis. Physical mixtures of Pt/alumina spheres and spherical zeolite particles are equivalent to catalysts with platinum deposited on the zeolite itself facilitating the investigation of the catalyst components individually. The spherical alumina particles are very convenient supports for obtaining a homogeneous distribution of highly dispersed platinum nanoparticles. Obtaining such a small Pt particle size is challenging on other support materials such as zeolites. The here reported and well-characterized Pt/alumina spheres can be combined with any zeolite and used as a bifunctional model catalyst. This is an interesting strategy for the examination of the acid catalytic function without the interference of the supported platinum metal on the investigated acid material.